1988
DOI: 10.2307/3430514
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Blood Lead Concentration in Bus Drivers

Abstract: San Francisco bus drivers have an increased prevalence of hypertension. This study examined relationships between blood lead concentration and blood pressure in 342 drivers. The analysis reported in this study was limited to subjects not on treatment for hypertension (n = 288). Systolic and diastolic pressures varied from 102 to 173 mm Hg and from 61 to 105 mm Hg, respectively. The blood lead concentration varied from 2 to 15 jig/dL The relationship between blood pressure and the logarithm of blood lead concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 15 publications
3
24
0
1
Order By: Relevance
“…Our data in children (21) are less likely to have such residual confounding because smoking and alcohol use are unlikely in children. Support for a Pb-blood pressure association derives from epidemiological data in occupational settings (71)(72)(73)(74) and animal studies (73,75). While the effect was not significant in our cohort, the consistency of the blood pressure findings with other studies, along with evidence from experimental studies, lead us to believe that continued Pb exposure may contribute to the incidence ofhypertension.…”
Section: Discussionsupporting
confidence: 58%
“…Our data in children (21) are less likely to have such residual confounding because smoking and alcohol use are unlikely in children. Support for a Pb-blood pressure association derives from epidemiological data in occupational settings (71)(72)(73)(74) and animal studies (73,75). While the effect was not significant in our cohort, the consistency of the blood pressure findings with other studies, along with evidence from experimental studies, lead us to believe that continued Pb exposure may contribute to the incidence ofhypertension.…”
Section: Discussionsupporting
confidence: 58%
“…Even though studies with high methodological quality ("xxxx" or "xxxxx") are few, the following conclusions seem reasonable on the basis of the existing epidemiologic literature: (i) there is a causal relationship between lead exposure and blood pressure even at low exposure levels corresponding to blood-lead levels below 30 ug/dl (27,28,31,70,73,74,106), and, even if the relationship is weak, this relationship may have considerable public health implications due to the widespread lead exposure throughout the industrialized world (32,72); (ii) there is an increased incidence of cerebrovascular diseases among workers who have been occupationally exposed to lead, but the clarification of the dose-response relationship is not possible on the basis of the existing studies; (iii) no studies have been found in which the incidence of ischemic heart disease (IHD) increased as a result of lead exposure.…”
Section: Leadmentioning
confidence: 99%
“…It is a known toxic substance that induces adverse health effects in multiple systems, including neurological, hematological and cardiovascular 1,2) . Most studies have indicated that environmental exposure to lead is associated with an increased risk of hypertension [3][4][5][6][7][8][9][10] . Our previous study found a relationship between blood lead level and hypertension among traffic policemen working in the eastern region of Thailand 11) .…”
Section: Introductionmentioning
confidence: 99%